Carry on, Mr. Bowditch - Latham, Jean Lee; Cosgrave, John O'Hara, II, 1908-1968 (Boston : Houghton Mifflin, 2003)
After finding a way to teach the ship's crew members to understand navigation, Nat, a self-taught mathematician and astronomer in eighteenth-century Salem, Massachusetts, writes down his explanations and compiles them into "The American Practical Navigator," also known as the "Sailors' Bible."
Angela Misa
Keywords: Bowditch, Nathaniel, -- Juvenile fiction; Bowditch, Nathaniel, -- Fiction; Mathematicians -- Fiction; Astronomers -- Fiction; Navigation -- Fiction; Seafaring life -- Fiction; Salem (Mass.) -- History -- 18th century -- Fiction